Influence of Unusual Co-substrates on the Biosynthesis of Medium-Chain-Length Polyhydroxyalkanoates Produced in Multistage Chemostat - Hanik, Nils; Utsunomia, Camila; Arai, Shuzo; Matsumoto, Ken'ichiro; Zinn, Manfred (Frontiers in Bioengineering and Biotechnology, 2019)
A two-stage chemostat cultivation was used to investigate the biosynthesis of functionalized medium-chain-length polyhydroxyalkanoate (mclPHA) in the β-oxidation weakened strain of P. putida KTQQ20. Chemostats were linked in sequence and allowed separation of biomass production in the first stage from the PHA synthesis in the second stage. Four parallel reactors in the second stage provided identical growth conditions and ensured that the only variable was the ratio of decanoic acid (C10) to an unusual PHA monomer precursor, such as 10-undecenoic acid (C11:1) or phenylvaleric acid (PhVA). Obtained PHA content was in the range of 10 to 25 wt%. When different ratios of C10 and C11:1 were fed to P. putida, the produced PHA had a slightly higher molar ratio in favor of C11:1 based 3-hydroxy-10-undecenoate. However, in case of PhVA a significantly lower incorporation of 3-hydroxy-5-phenylvalerate over 3-hydroxydecanoate took place when compared to the ratio of their precursors in the feed medium. A result that is explained by a less efficient uptake of PhVA compared to C10 and a 24% lower yield of polymer from the aromatic fatty acid (y_((PHA-M)⁄PhVA)=0.25). In addition, PHA isolated from cultivations with PhVA resulted in the number weight average ¯(M_n ) two times lower than the PHA produced by C10 alone. Detection of products from PhVA metabolism in the culture supernatant showed that uptaken PhVA was not entirely converted into PHA, thus explaining the difference in the yield polymer from substrate. It was concluded that PhVA or its related metabolites increased the chain transfer rate during PHA biosynthesis in P. putida KTQQ20, resulting in a reduction of the polymer molecular weight.